Modelling, simulation and resource optimisation of complex development project by fusion of multiple-domain matrix and coloured Petri nets methods. (2019) - Topic, Gordan; Jevtic, Dragan
In this research, a fusion of two methods is developed as a suitable strategy and procedure for dynamic management of complex project systems: the first method of multiple-domain matrix (MDM) includes modelling complex relations between resources and activities, using rearrangement of these elements to minimise feedbacks. The second method provides an insight into the project system dynamics by performing coloured Petri net (CPN) simulation based on the model of project system obtained by the first method. The focus is on the unique conversion of the MDM method to CPN, where the static system description of the MDM method was expanded by the capabilities of the dynamic system description of the CPN method. The objective was to evaluate an effective technique to analyse a complex project system of software development, which enables detailed planning and optimal management to shorten the production cycle of the appropriate quality with the lowest cost.